RURAL DISTRICTS AND SOCIAL REPRODUCTION STRATEGIES IN THE MUNICIPALITY OF PRESIDENTE PRUDENTE-SP - Santos, Marleide Silva Aristides dos [UNESP]; Hespanhol, Rosangela Ap de Medeiros [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2018)
The main focus of the article is the analysis of social reproduction strategies of family farmers from Bairros Rurais Aeroporto and Corrego da Onca, municipality of Presidente Prudente (SP). To accomplishthe research, we have done a bibliographical survey on the thematic and data collection of primary and secondary sources. The primary source data was obtained from semi-structured interviews with the presidents of the rural producers association of the two districts already mentioned above, as well as the employees of municipal and state public agencies. On the other side, the secondary source data was collected and systematized from digital available sources on IBGE and on SEADE databases. In this article, strategies of social reproduction are understood as decisions taken by rural families in the work-life field in rural property. It was found that this part-time activity (part-time agriculture) constitutes a possibility of improving monthly family's income the combination of agricultural and non-agricultural activities as a way to help financially struggling families, it also shows that it is not only within the properties that producers are seeking strategies of social reproduction; and productive diversification as a decision taken by the family.
Keywords: Strategies; Rural Neighborhood; Rural-Urban Ratio; Urban Sprawl; Municipality Presidente Prudente (SP)